A study on the dynamic relations between macro economic variables and stock market performance / Huzaimi Hussain, Jaafar Pyeman and Mohd. Mokhtar Ghani - Hussain, Huzaimi; Pyeman, Jaafar; Ghani, Mohd. Mokhtar (UiTM Shah Alam, Selangor, 2005)
The purpose of this study is to investigate the dynamic relationship between stock market performance and macroeconomic variables in Malaysia. The Kuala Lumpur Composite Index (KLCI) is used to proxy for the stock market performance and macroeconomic variables employed are three-month treasury bills rate, inflation rate, and economic growth as measured by gross domestic product. This study utilizes cointegration and causal relationship approach to accomplish the research objectives. The findings from this study exhibit that there are long run cointegration relationship between stock market performance and macroeconomic indicators. Moreover, results of further analysis generally show that all the indicators have substantial impacts on KLCI with the most immediate impact coming from treasury bills rate. In addition it is shown via the variance decomposition procedure that treasury bills rate is highly exogenous. The major policy implication of this study is that market performance can be monitored by Central Bank through treasury bills rate.